2015
DOI: 10.12705/643.6
|View full text |Cite
|
Sign up to set email alerts
|

A new cryptic species in a new cryptic genus in the Caesalpinia group (Leguminosae) from the seasonally dry inter‐Andean valleys of South America

Abstract: The generic affiliation of the Andean species Caesalpinia trichocarpa, C. mimosifolia, and their close relatives has remained uncertain in all recent studies of Caesalpinia s.l. (Leguminosae, subfamily Caesalpinioideae). A new densely sampled phylogeny based on four DNA sequence regions (rps16, trn D‐trnT, ycf6‐ psbM, ITS) strongly supports the monophyly of an Andean clade. We propose that despite the lack of obvious diagnostic morphological synapomorphies, this Andean group should be considered as a distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 73 publications
(73 reference statements)
1
24
0
1
Order By: Relevance
“…The Caesalpinia group was defined by Polhill and Vidal (1981) to include the genera with species that have a large variety of glandular trichomes, prickles and spines as a defense mechanism, and possessing zygomorphic flowers with a somewhat modified lower sepal and stamens crowded around the pistil. It is currently classified into 21 genera (Lewis 2005), but recent studies, and notably Gagnon et al (2013, 2015), have demonstrated the non-monophly of some of these and the need for a new generic classification (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Caesalpinia group was defined by Polhill and Vidal (1981) to include the genera with species that have a large variety of glandular trichomes, prickles and spines as a defense mechanism, and possessing zygomorphic flowers with a somewhat modified lower sepal and stamens crowded around the pistil. It is currently classified into 21 genera (Lewis 2005), but recent studies, and notably Gagnon et al (2013, 2015), have demonstrated the non-monophly of some of these and the need for a new generic classification (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…(Simpson et al 2006), Mezoneuron Desf. (Clark and Gagnon 2015), and Arquita E. Gagnon, G. P. Lewis & C. E. Hughes (Gagnon et al 2015). The most recent phylogenetic study (Gagnon et al 2013), based on a single plastid marker ( rps16 ) and sampling 120 of ca.…”
Section: Introductionmentioning
confidence: 99%
“…46 . For the most problematic samples, including those with large mononucleotide repeats, we used a PCR protocol with Phusion Hot Start II High-Fidelity DNA polymerase (Thermo Scientific, Waltham, Massachusetts, U.S.A.), which is more accurate and yields longer and higher-quality mononucleotide sequence reads 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the Akaike information criterion, the best models identified were GTR + I + G for ITS/5.8 S, TVM + G for matK/trnK and rpL16 , and TPM1 uf + G for trnG-trnG2G . Bayesian analyses were conducted in MrBayes v.3.2 65 , but because it is not possible to specify the exact models for the three plastid regions in MrBayes, we used the reversible-jump MCMC option, which allows sampling of different schemes of nucleotide substitution as part of the MCMC run (nst = mixed) 46 . The Bayesian estimation consisted of two independent runs during 50 × 10 6 generations, sampling trees and parameters every 1000th generation.…”
Section: Methodsmentioning
confidence: 99%
“…Adicionalmente, hay áreas importantes al sur de Tarapoto (departamento de San Martín) y en los bosques secos inter-andinos (BSI) ubicados en los valles de los ríos Marañón, Mantaro y Apurímac (Linares-Palomino, 2004, 2006. En los últimos diez años se ha generado valiosa información sobre los BSI (Särkinen et al, 2011;Särkinen et al, 2012;Gagnon et al, 2015;Marcelo-Peña et al, 2015); no obstante, aún se conoce poco sobre la biología de estos bosques secos, tanto en términos descriptivos (florísticos) como funcionales (ecológicos).…”
Section: Introductionunclassified